The medical and demographic situation in Russia: Long-term trends, prospects and improvement potential - O.S. Kobyakova; I.P. Shibalkov; I.A. Solomatnikov; S.A. Timonin; A.E. Shchur; M.D. Lagutin; D.S. Tyufilin; I.A. Deev; S.Yu. Nikitina (Analiz Riska Zdorovʹû)
Relevant trends for shaping state social policy, including public health protection, can only be formed relying on accurate assessment and forecast of changes in key medical and demographic indicators. Following the COVID-19 pandemic, which had both direct and indirect adverse effects on population mortality across the globe, interest in evaluating possible future changes in the medical and demographic situation has increased. According to the median projections by the United Nations Population Division and the Federal State Statistics Service, the population of the Russian Federation may decrease by 7.3–10 million people by the beginning of 2046. To reverse this negative trend, substantial efforts should be taken beyond migratory growth, including finding innovative mechanisms to stimulate birth rates and reduce mortality (increase life expectancy at birth) as the primary components influencing natural population growth and, consequently, population dynamics.